PENGUNGKAPAN TATA KELOLA DAN AKUNTABILITAS LAPORAN KEUANGAN TERHADAP LEMBAGA AMIL ZAKAT, INFAQ DAN SHADAQAH MUHAMMADIYAH KABUPATEN GOWA (LAZIZMU KAB. GOWA) - Rahman, Taufiq; suarni, Agusdiwana (Jurnal Ar-Ribh, 2019)
This study determines how the governance of financial statements and accountability of financial statements. The Law of the Republic of Indonesia Number 23 of 2011 concerning Zakat Management, in which the Law regulates in sufficient detail the functions, roles and responsibilities of the Board of Amil Zakat (BAZ) and the Amil Zakat Institution (LAZ). This type of research used in research is qualitative. Data collection techniques carried out by the author, namely by documentation and interviews with 3 staff respondents LAZIZMU Gowa. The finding of this research is that the organizational system of the Muhammadiyah amil zakat institution in Gowa Regency is categorized as good and the collection of ZIS funds is considered good, it can be seen from the achievement of ZIS fund collection in 2017 which reached Rp. 159,549,950. which in 2016 was only around Rp. 34,960,000 because the Amil Zakat, Infaq and Shadaqah Muhammadiyah institutions of Gowa Regency have not collected ZIS funds that have not reached the target, due to the large number of Zakat Collecting Institutions in Gowa Regency.Keywords: Governance, Accountability, Financial Statements, LAZISMU